The initial results of MRI-TRUS fusion prostate biopsy in high volume tertiary center - Smrkolj Tomaz; Taskovska Milena; Ditz Iztok; Cernelc Klemen; Hawlina Simon (Radiology and Oncology)
Multiparametric magnetic resonance imaging (mpMRI) is a prerequisite for targeted prostate biopsy. The aim of our study was to evaluate the performance and learning curve of the mpMRI-transrectal ultrasound (TRUS) software image fusion (MRI-TRUS fusion) biopsy (BX) process in the first year after its introduction in our urology department.